Another Fateful Triangle: Jews, Muslims, Europe - Elisabeth Jane Becker (Religions)
This paper argues that Jews–Muslims–Europe is a fateful triangle, in which identities and identifications both inform and form one another. It draws on interview-based research at the Jewish Museum Berlin to showcase how Jewish and Muslim positionalities have become entwined in the context of contemporary Berlin, Germany, and Europe. At the same time, it showcases how the positionality of strangerhood can provide a critical perspective for understanding and articulating Europe as a place of pluralism, both present and past. What emerges is a sociocultural terrain in which Muslims, Jews, and Europe are made by and with one another, rather than simply against one another.